Design of a Fault Tolerant Digital Communication System, by Means of Rbf Networks. Comparison Simulations with the Encoding and Decoding Algorithms Bch (7,4,1) - Jamett-Dominguez, M; Urrea-Onate, E; Kern-Molina, J (IEEE Computer Society, 2014)
This paper presents the design of a BCH encoder (7,4,1) and BCH decoder (7,4,1) with Radial Basis Neural Network as error correction technique for fault tolerant systems, applied in digital communications. The neural network model is exported to Matlab Simulink to test different scenarios, to achieve results equivalent to those described by the BCH algorithm, in an empirical and scalar way. © 2014 IEEE.